Current situation and development trend of gait recognition - Yingzhao ZHU; Man LI (Dianxin kexue)
Gait recognition is an advanced technology in the field of biometric identification.In view of the advantages of long-distance identification,uncontrolled identification and difficult camouflage,it has great potential to promote the development of pattern recognition,image processing,treatment and recovery.Firstly,the key technologies,research status and the common databases of gait recognition were introduced.Then,its application prospect was analyzed.Finally,the development trend of gait recognition was judged.